To Eat or Not to Eat? The Modern Consumption Model Through the Prism of Food Wasting: Moscow Citizens Case - Daria Asaturian; Valeriya Erguneva (Journal of Economic Sociology, 2018)
Following Western and American trends, modern Russian society is going through a change in consumption patterns, particularly related to food products. After Russia’s transition from a “deficit society” to “a society of (over)consumption,” the question regarding the further direction of development arises. If Western countries are now moving toward “conscious consumption,” which is ideologically based on environmental concerns, then Russia has yet to make a choice. In this regard, it is necessary to understand how Russian food management will develop in the future. For this paper, an indicator often bypassed by researchers in the study of nutrition practices was chosen—food wasting. This research is based on 22 in-depth interviews and attempts to identify the semantic contexts that keep informants from wasting food or that stimulate food waste food. According to the results of the study, it became clear that, in addition to the expected rational attitudes tied to the optimization of food management, this issue is interpreted in terms of informants’ values, coupled with the social embeddedness of their practices of throwing out or saving food products, whose roots originate in the Soviet past and are transmitted from generation to generation.